Topical prostaglandin analogue use and cystoid macular oedema following uneventful cataract surgery: a randomised control trial. Issue 12 (27th May 2021) - Niyadurupola, Nuwan; Brodie, James; Patel, Tejal; Chan, Jason; Rahman, Mohammad M; Svasti-Salee, Carl R; Ching, Jared; Misra, Aseema; Eke, Tom; Broadway, David C
Abstract : Background/aims: The association between the development of cystoid macular oedema (CMO) following uneventful cataract surgery and prostaglandin analogue (PGA) therapy has not been fully determined. The study aim was to investigate whether discontinuation of PGA therapy following uneventful cataract surgery affected the incidence of postoperative CMO. Methods: A prospective randomised controlled trial of 62 eyes of 62 participants with ocular hypertension (OH) or primary open angle glaucoma (POAG) treated with PGAs prior to cataract surgery. Participants were randomised to continue with PGA therapy after cataract surgery (CPGA) (n=31) or to discontinue PGA therapy (n=31). The primary outcome measure was the development of CMO at 1-month postoperatively, determined by a masked observer assessment of optical coherence tomography scans. The secondary outcome measure was change from baseline intraocular pressure (IOP). Results: The incidence of CMO was identical in both groups at 12.9% (4 of 31 eyes) at the 1-month postoperative visit (OR 1.000; 95% CI 0.227 to 4.415). At 1-month postoperatively, the IOP was significantly lower in the CPGA group compared with baseline IOP. Conclusion: Continuation of PGA therapy following uneventful cataract surgery in eyes with normal macular morphology did not increase the incidence of CMO. Continuation of PGA therapy significantly reduced IOP at 1-month postoperatively suggesting that, when indicated, it might be beneficial to continue PGA therapy in patients with POAG or OH after uneventful cataract surgery in the absence of other risk factors for developing CMO.